Minimum environmental load extension through compressed air extraction: Numerical analysis of a dry low NOx combustor. (15th April 2023) - Yudha Wiranegara, Raditya; Igie, Uyioghosa; Ghali, Pierre; Abudu, Kamal; Abbott, David; Hamilton, Richard
Highlights: Combustor can handle minimum environmental load extension with airflow extraction. Up to 7% points load reduction is possible when translated in engine-level analysis. CO reduces by 12% with a necessary increase of fuel spit ratio by 2% NO increases by 5% in relation to the peak values in normal operation at part-load. Combustor flame durability and stability do not appear to be significantly altered. Abstract: The operational flexibility of gas turbine (GT) engines is a key requirement to coexist alongside increasing renewable energy that is often intermittent. One of the GT flexibility criteria is the Minimum Environmental Load (MEL). This is the lowest load the engine can be operated, without infringing on emissions limits (particularly CO) and is relevant to periods when there is a priority to renewable generation or low power demand. This study along with a series of related works of the authors proposes compressor air extraction for MEL extension. Here, a stand-alone three-dimensional numerical dry low NOx combustor demonstrates the technical viability concerning combustor performance and emissions. In addition, supplemented with low-order models for durability and stability evaluations. For the first time, there is evidence to show that the combustor can handle the 18% compressed air extraction to sustain a new MEL. This operation is characterised by a 12.3% reduction in CO through an increase of the fuel split ratio by 2% after design exploration cases. However, at the expense of a smaller overall rise in NO emissions by 5%. The durability analysis focused on the wall liner temperature assessments, which show no unusually high temperature rise for the new MEL. Similarly, the thermoacoustic instability frequencies and gains are around the normal operation mode. When benchmarked against previous related engine-level analysis, the evidence shows that the new MEL is a 7% points reduction of load.